2015
DOI: 10.1210/jc.2014-2682
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Damage Is Associated With Inflammatory Markers and Worse Cognitive Performance in Obese Subjects

Abstract: Context:Growing evidence implicates hypothalamic inflammation in the pathogenesis of dietinduced obesity and cognitive dysfunction in rodent models. Few studies have addressed the association between obesity and hypothalamic damage in humans and its relevance.Objective: This study aimed to determine markers of obesity-associated hypothalamic damage on diffusion tensor imaging (DTI) and to determine whether DTI metrics are associated with performance on cognitive testing. Outcome: measures: Hypothalamic damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 22 publications
4
42
0
1
Order By: Relevance
“…This inflammation then causes synaptic remodeling and degeneration in hypothalamus, thereby affecting any regions to which the hypothalamus projects, including brain regions important in cognition (Miller and Spencer, 2014). Additionally, greater hypothalamic damage was associated with higher levels of inflammatory cytokines and worse cognitive performance in obese subjects (Puig et al, 2015). …”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%
“…This inflammation then causes synaptic remodeling and degeneration in hypothalamus, thereby affecting any regions to which the hypothalamus projects, including brain regions important in cognition (Miller and Spencer, 2014). Additionally, greater hypothalamic damage was associated with higher levels of inflammatory cytokines and worse cognitive performance in obese subjects (Puig et al, 2015). …”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%
“…Moreover, obese patients appear to have reduced integrity of vital brain circuits, correlating with levels of peripheral inflammation and cognitive dysfunction. These findings suggest that an anatomical mechanism may link increased adiposity with CNS impairment [104, 105]. …”
Section: Gliosis and Obesity In Humansmentioning
confidence: 99%
“…A separate MRI study in 44 overweight/obese subjects reported an inverse correlation between systemic inflammation (measured as serum fibrinogen) and the integrity of brain structures involved in food reward and feeding behavior (73). Most recently, diffusion tensor imaging (DTI) was used to screen for hypothalamic damage in 44 obese patients and controls (74••). In the obese cohort, lower axon diffusivity (i.e.…”
Section: Hypothalamic Pathology In Humans?mentioning
confidence: 99%